The Potential of Religious Radicalism Movement in Banyumas - Rindha Widyaningsih; S Sumiyem; K Kuntarto (Walisongo: Jurnal Penelitian Sosial Keagamaan, 2017)
Religious radicalism is the trigger for the occurrence of terrorism which is an extraordinary crime and an enemy of all the countries that exist in the world. Since Indonesia as a country has a high vulnerability to religious radicalism, it is important to conduct studies on religious radicalism both nationally and regionally. Knowing the level and potential of religious radicalism is a step for the creation of a comprehensive mechanism of prevention and treatment of religious radicalism. The position of Banyumas as an inter-provincial gateway becomes very strategic for radical groups to spread their ideology and mindset. The ease of inter-regional access underpinned by good supporting facilities and infrastructure is an important point of consideration for radical groups to spread their ideas. Interviews were conducted to obtain data from stakeholders who handle radicalism. the findings were elaborated with supporting literature to provide a more comprehensive result. The results of this study indicate that Banyumas has great potential for the growth and development of religious radicalism, and Banyumas people have high vulnerability to get exposed and influenced by the idea of radicalism caused by factors of religious behavior, geography, culture, technology and information development, and demography. However, so far the level of religious radicalism in Banyumas is still low because there is good cooperation between the stakeholders and the community.